Education supply chain: A case study of input-process-output of high technical vocational education and training (HTVET) - Hassan, Sallaudin; Shafiq, Ahmad; Firdaus, Khairul; J, Jimisiah. (International Journal of Engineering and Technology, 2018)
This study aim to explore in more depth on the Education Supply Chain targeted at three main stages which is Input, Process and Output. At input level, this study assess the factors effecting the enrolment. Further to this, at process level, this study assess the variable contributing the quality of graduate. Finally, at Output stage, this study obtaining feedback from industries on the quality industrial training student. This study is conducted in University Kuala Lumpur (UniKL), Malaysia Institute of Industrial Technology (MITEC) and 40 companies who involve in Industrial Training placement. Survey questionnaire is used for data collection. Result is processed using SPSS version 21. LIKERT scale is used by respondent to provide the assessment. Results shows at input stage, Financial Aids by MARA, is the main reason of student enrolment. This is followed by fees rate, entry requirements and promotion efforts by the marketing. At process stage, self-motivation is the most influence factor toward the graduate performance. It is followed by lecturer's approach, curriculum design, and studentâ€™s ability. At output stage, the industries provide their rating towards the quality of industrial training. Nine domain is used for assessment. The results show that the highest mean score is Value, Attitude & Professionalism (4.14). This is followed by Information Management and Lifelong learning Skills, Social Skill and responsibilities, Knowledge, Team work, Practical Skills, Managerial and Entrepreneurial Skill, Problem Solving & Scientific Skills and communication skills. It is recommend that further research to be done at output level since in order to gain more informative input toward reducing the gap between HTVET offering and demand from industries.Â Â